Pupils’ didactical Mileu in an inclusive discourse in basic triangle geometry - Ali, Clement Ayarebilla; Asemani, Emmanuel; Tangkur, Michael (Universitas Terbuka, 2024)
The concept of inclusivity is the practice of placing pupils with disabilities in normal classrooms. However, the idea of the triangle continues to pose fundamental challenges. This study sought to explore didactical mediation on the learning of the triangle beyond the classroom. The research design used mixed methods sequential exploratory to help identify the pupil’s triangle interpretation. The researchers first conducted a semi-structured interview on their experiences in learning the triangle both in school and at home. The responses were transcribed and coded in themes. The themes that emerged were properties, types of angles, and applications to everyday life. The researchers then went further to test the pupils’ knowledge on the same themes. The findings showed that didactical mediation with the cultural artifacts, signs, and language largely explained the emergence of the four main properties and must be targeted for the theory, policy, and practice of inclusive education. The prototype testing also confirmed that even though pupils with hearing impairment obtained higher scores, both groups obtained higher mean scores on the post-test than did the pre-test. This indicated that the learning achievement was significantly higher in the post-test than in the pretest due to the didactical mediation. It was recommended that the triangle’s learning and teaching should not be limited to academic exercises but to real-life situations. Also, not visually friendly mathematics concepts should be explored to uncover the most suitable methods and techniques to make inclusive mathematics learning a reality for all groups of disabilities.